Muslim Consumer Protection in the Era of E-Commerce: A Regulatory and Social Review : Perlindungan Konsumen Muslim dalam Era E-Commerce: Tinjauan Regulasi dan Sosial - Abdul Hapiz Mursidin Syabani; Hilmi Wardatusyafaqoh; Rifqi (Penerbit Hellow Pustaka, 2025)
The expansion of e-commerce in Indonesia has progressed rapidly in recent years; however, this growth has not been fully aligned with the values of Islamic Sharia, despite Indonesia having the world’s largest Muslim population. This study seeks to explore the legal and social consequences of implementing halal e-commerce in the Indonesian context and assess how well these practices conform to existing national regulations. Utilizing a normative legal research method, the study adopts conceptual, comparative, and content analysis approaches, drawing from Islamic legal sources and statutory law. The findings indicate that there is currently no comprehensive legal framework specifically governing halal e-commerce, leading to regulatory gaps and insufficient protection for Muslim consumers. On the social front, low levels of halal digital literacy and limited access to halal certification (particularly among micro, small, and medium enterprises (UMKM)) pose significant obstacles. The study emphasizes the need for strengthened halal digital regulations, the development of a tech-based certification infrastructure, and active collaboration between government agencies, business sectors, and religious authorities. In conclusion, the advancement of a sustainable halal e-commerce ecosystem requires an integrated strategy that encompasses legal, social, and technological elements to ensure Sharia compliance and inclusivity for Indonesia’s Muslim population.